The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.5194/acp-15-9693-2015
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and diurnal trends in black carbon properties and co-pollutants in Mexico City

Abstract: Abstract. The Mexico City metropolitan area (MCMA) is a region that continues to grow in population and vehicular traffic as well as being the largest source of short-lived climate pollutants (SLCP) in Latin America. The local city government has made significant progress in controlling some of these pollutants, i.e., ozone (O 3) and carbon monoxide (CO), but particulate matter (PM 2.5 and PM 10 ) and black carbon (BC) have shown a less positive response to mitigation strategies that have been in place for al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…More recently, Paredes-Miranda et al [106] compared the daily variation of BC absorption and scattering coefficients in five cities around the world and found that Mexico City has the highest values. Retama et al [107] analyzed one-year equivalent BC data (from March 2013 to March 2014) collected at SEDEMA's laboratory, which is not too far from the urban supersite during MILAGRO, and found a strong seasonal variation. The observed concentrations did not differ substantially from those of previous field campaigns, suggesting no major changes in the BC emissions.…”
Section: Aerosol Radiative Propertiesmentioning
confidence: 99%
“…More recently, Paredes-Miranda et al [106] compared the daily variation of BC absorption and scattering coefficients in five cities around the world and found that Mexico City has the highest values. Retama et al [107] analyzed one-year equivalent BC data (from March 2013 to March 2014) collected at SEDEMA's laboratory, which is not too far from the urban supersite during MILAGRO, and found a strong seasonal variation. The observed concentrations did not differ substantially from those of previous field campaigns, suggesting no major changes in the BC emissions.…”
Section: Aerosol Radiative Propertiesmentioning
confidence: 99%
“…The control cities have <75,000 inhabitants and, because of their small size, their levels for the main criteria air pollutants (ozone, particulate matter as PM 10 and PM 2.5 , sulfur dioxide, nitrogen dioxide, and carbon monoxide) are expected to be lower than the current US EPA standards. MC is an example of extreme urban growth and accompanying environmental pollution [65]. The metropolitan area of over 2,000 km 2 lies in an elevated basin 2,200 m above sea level surrounded on three sides by mountain ridges.…”
Section: Study Cities and Air Qualitymentioning
confidence: 99%
“…For this study, we included MC residents from the northern-industrialized and southern-residential zones. Northern residents have been exposed to higher concentrations of volatile and toxic organic compounds, PM 10 and PM 2.5 including high levels of its constituents: organic and elemental carbon, nitro-and polycyclic aromatic hydrocarbons, and metals (Zn, Cu, Pb, Ti, Mn, Sn, V, Ba), while southern residents have been exposed continuously to significant and prolonged concentrations of ozone, secondary aerosols (NO 3 − ), and PM associated with lipopolysaccharide [17,51,57,60,65]. The highest concentrations occur in the NE sector where industrial and traffic activities are prevalent, and decreased toward the SW residential area.…”
Section: Study Cities and Air Qualitymentioning
confidence: 99%
“…In general, this season is followed by a warm-dry period until May, when the rainy season starts and extends until October with an average annual rainfall of more than 1000 mm [21].…”
Section: Acu15 Campaignmentioning
confidence: 99%